Determinación de las competencias organizacionales de las mipymes agroproductivas procesadoras de lácteos de la zona norte de Manabí - Bravo Alcívar, José Wilfrido (2020)
The objective of this work is to determine the organizational competences for the agro-productive MIPYMES processing dairy products in the northern zone of Manabí in contribution to the management of the recruitment of human talent; the methodological design was developed through qualitative-quantitative, bibliographic and field research which allowed the collection of information and the display of findings of the object under study, methods as descriptive, inductive and deductive were used since the general characteristics collected possess the organizational competences and were specifically applied in the MIPYMES of the dairy processing sector, the techniques and tools that supported the management of the information were the interview, survey, the characterization matrix, thus promoting the obtaining of data that was subsequently analyzed using computer systems such as the SPSS, Excel and Google Forms, the process of selection of competences for MIPYMES processing dairy was carried out using the Dhelpi method, resulting in 9 competencies, the sample for the evaluation process was obtained by means of a simple random sampling, leaving the Havana dairy processor selected as MIPYMES, whose competencies according to their requirements were: ethics, customer orientation, quality of work, initiative and empowerment, which were submitted to evaluation to measure the level of development, thus allowing the proposal of a Competency Manual for this particular MIPYMES.